Effect of time and placement method of ammonium sulphate and superphosphate on the comparative efficiency of N and P absorption and N utilization in 'Robusta' banana (Musa Xparadisiaca) using labelled fertilizers - MURTHY, S V KESHAVA; KOTUR, S C (The Indian Journal of Agricultural Sciences, 2013)
An field experiment was conducted on 'Rabusta' banana (Musa xparadisiaca L.) during 1989-94 to study the effect of time of application and method of placement of phosphorus fertilizers and time of application of nitrogen fertilizer on the efficiency of absorption of N and P and utilization of N using 32p labelled single superphosphate and 15N labelled ammonium sulphate. Nitrogen (200 g/plant) in 4 equal splits and phosphorus (26.2 g/plant) in 1, 2 or 3 equal splits were applied at early vegetative (50 days), late vegetative (100 days), bud differentiation (180 days) and shooting stage. Single superphosphate was applied in 25 cm circular bands between 25-50 em and 50-75 em radial distances at early and late vegetative stages and between 25-50, 50-75 and 75-100 em radial distances during shooting stage whereas ammonium sulphate was applied between 25-50 em at early vegetative stage and between 25-75 em at other stages of plant growth. Absorption of N and P was monitored by leaf sampling at regular intervals and analysing the samples for 14N/ 15N ratio and specific activity of 32P. Utilization of fertilizer N was calculated by sampling the whole plant and analysis at the time ofbunch harvest. Absorption of fertilizer N [nitrogen derived from fertilizer (%)] and P [Phosphorus derived from fertilizer (%)] was faster when applied early at and late vegetative stages than when applied at later stages of plant growth. Fertilizer N applied at late vegetative stage gave the highest (60% nitrogen derived from fertilizer). However, N applied at later stages, viz at bud differentiation and shooting could maintain higher proportion of fertilizer N (18.5 - 22.5%) in the plant till bunch harvest compared to early and later vegetative stage application (6.0 - 16.3%). Uptake and utilization of fertilizer N also increased. at later stages of application and the highest N utilization was obtained from application at shooting (33.91%) and more of it was also partitioned to fruits (22.49%). In the case of phosphorus application at early and late vegetative stages resulted in higher phosphorus derived from fertilizer (8.36 to 12.90%) as against at shooting (2.76%). At early and late vegetative stages placement in 25 cm circular bands around the plant between 25-50 cm radial distances resulted in higher phosphorus derived from fertilizer (8.36 and 12.9%) compared to placement at 50-15 cm (8.16%). Thus it is recommended to apply phosphorus in 2 equal splits, once on the 50th day (8th leaf stage) and again between 160-180 days after planting (bud differentiation stage) and N in 4 equal splits, viz SO, 100, 160-180 dayS after planting and at shooting.